Enthalpies of formation of piperazinium dinitrate, C4H12N2(NO3)2, dichloride, C4H12N2Cl2, and dichloride monohydrate, C4H12N2Cl2·H2O. (November 2022) - Tsvetkov, Dmitry S.; Mazurin, Maxim O.; Malyshkin, Dmitry A.; Sereda, Vladimir V.; Ivanov, Ivan L.; Zuev, Andrey Yu.
Highlights: Standard formation enthalpies of piperazine salts: C4 H12 N2 (NO3 )2, C4 H12 N2 Cl2 and C4 H12 N2 Cl2 ·H2 O at 298.15 K were determined. Hydration enthalpies of piperazinium dichloride by gaseous and liquid water were calculated. Δf H°298 of aqueous C4 H12 N2 2+ ion was estimated. Abstract: Standard formation enthalpies of some solid piperazine salts: C4 H12 N2 (NO3 )2, C4 H12 N2 Cl2 and C4 H12 N2 Cl2 ·H2 O at 298.15 K were measured using combustion and solution calorimetry. The following values were obtained: Δ f H 298 ° (C4 H12 N2 (NO3 )2 ) = (-594.4 ± 2.7) kJ·mol −1, Δ f H 298 ° (C4 H12 N2 Cl2 ) = (-475.6 ± 2.9) kJ·mol −1, Δ f H 298 ° (C4 H12 N2 Cl2 ·H2 O) = (-772.3 ± 2.9) kJ·mol −1 (expanded uncertainties, 95% confidence level). The hydration enthalpies of piperazinium dichloride by gaseous and liquid water were found to be equal to (-54.82 ± 0.09) kJ·mol −1 (H2 O) and (-10.83 ± 0.09) kJ·mol −1 (H2 O), respectively (expanded uncertainties, 95% confidence level). The results obtained allowed estimating Δ f H 298 ° of aqueous C4 H12 N2 2+ ions as (-128.5 ± 2.9) kJ·mol −1 (expanded uncertainty, 95% confidence level), which is in good agreement with the value of (-129.0 ± 3.3) kJ·mol −1 (expanded uncertainty, 95% confidence level) that was calculated using the literature data.